The Impact of Digital Transformation on Traditional Banking Efficiency: A Case Study of Postbank Mukono Branch - Vanessa Tsongo Kasoki (Uganda Christian University, 2024)
This study evaluated the impact of digital transformation on traditional banking efficiency, focusing on the Postbank Mukono Branch. Employing a mixed-methods approach, the research combined quantitative surveys and qualitative interviews to assess the effects of digital payment methods, mobile banking, and online banking on traditional banking metrics. Key metrics included customer satisfaction, a reduction in physical branch visits, and an increase in the number of new accounts opened. Findings revealed that, Postbank Mukono Branch has made notable progress in its digital transformation journey, enhancing the efficiency and convenience of banking services. By addressing the identified challenges and implementing the recommended strategies, the bank can further improve customer satisfaction and fully realize the benefits of digital banking. It will not just make the bank more competitive, but it will also help in meeting changing needs of customers in the dynamic environment of financial institutions.
Undergraduate Research